Penerapan Enkripsi AES-256 Untuk Pengamanan Data Pada Website Layanan Administrasi Desa Cantik - Febiola, Febiola; Kasmawi, Kasmawi; Hidayasari, Nurmi (Jurnal Ilmiah Teknologi Informasi Asia, 2026)
Data security in village administration service systems is a critical concern, as these systems manage sensitive personal information such as full names, National Identity Numbers (NIK), Family Card (KK) numbers, addresses, and supporting documents. Many existing village administration systems store such data without adequate protection, increasing the risk of data leakage, identity theft, and unauthorized access. This study implements the Advanced Encryption Standard (AES-256) algorithm to enhance data security in a village administration services website. The research methodology includes system requirements analysis, system design, AES-256 implementation for personal data and document encryption, and functional and performance evaluation. The system automatically encrypts all sensitive data before storing it in the database and decrypts it only for authorized administrators. In addition, the system supports secure processing of statistical Excel files to facilitate the Desa CANTIK program. Experimental results show that the proposed system provides strong data protection with minimal performance overhead, averaging less than 120 ms for encrypting and decrypting 5 MB files, while maintaining acceptable CPU and memory usage. These results indicate that AES-256 can be effectively integrated into village administration services to improve data security without compromising system efficiency.